Religious freedom and objectives for economic intercultural development (Stato, Chiese e pluralismo confessionale, 2013)
Text, accepted by the Director, of the report presented at the International Consultation on Religious Freedom Research (Istanbul on 17 March 2013), supervised by Prof. Antonio Fuccillo. This text was admitted after being assessed by the members of the evaluation scientific committee of the International Institute of Religious Freedom.SUMMARY: 1. The theory of public goods: religious freedom as a public good – 2. Economics and religion: the reasons for the need of intercultural relationship – 3. Religious factors and asymmetric information in economics – 4. Ethical development, religion and the cross-cultural domain – 5. Financial choices and religious factors – 6. Concluding remarks.